1986
DOI: 10.1212/wnl.36.12.1584
|View full text |Cite
|
Sign up to set email alerts
|

Association of low blood manganese concentrations with epilepsy

Abstract: A comparison of hospitalized epileptic patients with matched normals showed that the mean whole blood manganese (Mn) concentration of the epileptic population was significantly lower than the mean of the normal population. The whole blood Mn concentration in the epileptics did not correlate either with seizure frequency or with anticonvulsant therapy. It was observed, however, that patients whose epilepsy was a result of trauma had significantly higher blood Mn concentrations than patients whose history was ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…On the other hand, the conclusion by Carl et al (1986Carl et al ( , 1990) that differences in Mn2+ concentrations are related to genetically determined susceptibility to seizures are supported by our data indicating that glutamine synthetase activity is lower in brains of epileptic animals than in nonepileptic controls, paralleling an earlier observation (Carl et al, 1990) showing lower Mn2+ levels in brain of epilepsyprone animals. Although initially the seizure effect on Mn2+ concentrations appeared to explain the several observations of low Mn2+ blood levels in epileptic persons (Dupont and Harpur 1977;Papavasiliou et al, 1979;Dupont and Tanaka 1985;Carl et al, 1986;Akram et al, 1989) it now appears that even though that effect is real it is not the only relation between epilepsy and Mn2+. Our data appear to show that a relation exists between Mn2+ Table 4.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, the conclusion by Carl et al (1986Carl et al ( , 1990) that differences in Mn2+ concentrations are related to genetically determined susceptibility to seizures are supported by our data indicating that glutamine synthetase activity is lower in brains of epileptic animals than in nonepileptic controls, paralleling an earlier observation (Carl et al, 1990) showing lower Mn2+ levels in brain of epilepsyprone animals. Although initially the seizure effect on Mn2+ concentrations appeared to explain the several observations of low Mn2+ blood levels in epileptic persons (Dupont and Harpur 1977;Papavasiliou et al, 1979;Dupont and Tanaka 1985;Carl et al, 1986;Akram et al, 1989) it now appears that even though that effect is real it is not the only relation between epilepsy and Mn2+. Our data appear to show that a relation exists between Mn2+ Table 4.…”
Section: Resultssupporting
confidence: 90%
“…Malecki and Greger found that lipid peroxidation was greater in rat heart mitochondria in animals deficient in Mn compared to rats receiving adequate amounts of manganese, which inversely correlated with MnSOD activity [252]. Manganese deficiency has been identified in patients with sundry diseases, including epilepsy [253], diabetes mellitus [254], and patients receiving hemodialysis [255]. Future studies of how this manganese deficiency correlates with MnSOD activity and lipid peroxidation in these, and other, diseases may provide important insights into mechanisms of disease development.…”
Section: Effects Of Mnsod On Mitochondrial Integrity/functionmentioning
confidence: 99%
“…Calcium is an important intracellular messenger and is involved in many neuronal processes including short-term memory (Dash et al., 2007). Manganese ions are toxic to neuronal cells at high concentrations (Perl and Olanow, 2007), and manganese deficiency is linked with epilepsy (Carl et al., 1986). CMIP was identified through a screen to identify large proteins expressed in the brain (Nagase et al., 2000) and encodes an adaptor protein thought to form part of the cytoskeleton (Grimbert et al., 2003).…”
Section: Main Textmentioning
confidence: 99%